Application Of Green Technology In Gelatin Extraction: A Review - Nor Qhairul Izzreen Mohd Noor; Rina Syafinaz Razali; Nur Khairina Ismail; Rabiatul Amirah Ramli; Umi Hartina Mohamad Razali; Ahmad Riduan Bahauddin; Nazikussabah Zaharudin; Ashari Rozzamri; Jamilah Bakar; Sharifudin Md Shaarani (MDPI, 2024)
Indexed by Scopus/ERA